EFEK PERPADUAN BEBERAPA TUMBUHAN LIAR DI SEKITAR AREA PERTANAMAN PADI DALAM MENARIK ARTHROPODA MUSUH ALAMI DAN HAMA - Addina, Lu’aili (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2013)
This study aims to determine the interest Arthropoda against some wild mix consisting of Chromolaena odorata, Bidens pilosa., Echinochloa Cruss-galli, and Pistia stratiotes. This research is a semi experimental parameters observed were differences in the abundance of arthropods in each observation plot good plot consisting of some combination of wild plants (block refugia) and plot a block away from refugia based on spatial and temporal distribution. Observations using the